2015
DOI: 10.1074/jbc.m115.690784
|View full text |Cite
|
Sign up to set email alerts
|

C1q Deficiency Promotes Pulmonary Vascular Inflammation and Enhances the Susceptibility of the Lung Endothelium to Injury

Abstract: The collectin proteins are innate immune molecules found in high concentrations on the epithelial and endothelial surfaces of the lung. While these proteins are known to have important anti-inflammatory actions in the airways of the lung little is known of their functional importance in the pulmonary circulation. We recently demonstrated that the circulating collectin protein adiponectin has potent anti-inflammatory effects on the lung endothelium, leading us to reason that other structurally related proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Studying endothelial function: previous studies have shown that cultured MLECs can be used for multiple assays for assessing endothelial function, such as angiogenesis 28 , vascular tone 29 , and inflammation 30 . Here, we used LPS induced inflammatory response and monocyte adhesion as a model to test the responsiveness of cultured cells.Validation of endothelium-specific knockout or transgenic mice as well as performing phenotypic, genetic, or proteomic studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studying endothelial function: previous studies have shown that cultured MLECs can be used for multiple assays for assessing endothelial function, such as angiogenesis 28 , vascular tone 29 , and inflammation 30 . Here, we used LPS induced inflammatory response and monocyte adhesion as a model to test the responsiveness of cultured cells.Validation of endothelium-specific knockout or transgenic mice as well as performing phenotypic, genetic, or proteomic studies.…”
Section: Discussionmentioning
confidence: 99%
“…6D. A recent study demonstrated that targeted deletion of C1q in mice alters pulmonary vascular homeostasis by augmenting the expression of endothelial adhesion markers associated with enhanced susceptibility of the lung endothelium to injury (49). To examine the potential mechanism by which fibrosis was still observed in C1qA Ϫ/Ϫ mice, we measured mRNA levels of two adhesion molecules involved in endothelial cell injury, ICAM-1 and VCAM-1.…”
Section: F521mentioning
confidence: 99%
“…Lung tissue was dissociated into a single-cell suspension using a mouse lung dissociation kit (Miltenyi Biotec, Bergisch Gladbach, Germany) with the gentle gentleMACS dissociator (Miltenyi Biotec, Bergisch Gladbach, Germany), as previously described (19). The purity of the endothelial cell population was confirmed by flow cytometry, as previously described (17).…”
Section: Lung Endothelial Cell Isolationmentioning
confidence: 99%